My Experience Regarding to Hydatidiform Mole as a Precancerous Condition - Shamshiri Milani, Hourieh (Asian Pacific Journal of Cancer Biology, 2017)
In 1983, when I was in the first year of residency in Obstetrics and Gynecology, an eighteen years old mother died by invasive mole. Since the past 30 years, Mole hydadidiform (HM) as the origin of more invasive forms of Gestational Trophoblastic Neoplasia (GTN) which affects women’s health, has been as one of my concerns and I would like to share my perception and experience in this way with you.